Pengaruh Perbedaan Transportasi Sistem M-CLOVE dengan Konvensional dan Jenis Kelamin terhadap Respon Fisiologis Ayam Broiler - Pratama, T. A. I. P.; Yani, A.; Afnan, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
Meat consumption in Indonesia has increased with most needs come from broiler meat. However, it is not followed by development of the transportation technology that consider animal welfare. The purpose of this study was to compare the level of broiler stress measured from comb, shank and rectal temperature among sex between conventional transport system and environmentally transportation M- CLOVE. The results showed average of temperature and relative humidity during the transport process in the M-CLOVE was lower compared to the open crate. Temperature differences occured 1.4 °C with a relative humidity of 2.5% different. M-CLOVE transport reduced the level of stress of broiler which was indicated from lower comb temperature, shank temperature and rectal temperature which compared to broiler transported in open crate. Closed system and constant air circulation in the M-CLOVE might reduce the effects of heat generated from exposure to direct sunlight during the transportation process.